APLIKASI SISTEM PENDUKUNG KEPUTUSAN ANALISIS KELAYAKAN PEMBERIAN KREDIT MENGGUNAKAN METODE SAW PADA PERUSAHAAN LEASING - Siti Aisyah (LPPM Politeknik LP3I Medan, 2019)
One of actual problems faced by leasing companies in granting credits to their customers is the risk of bad debts. To overcome this problem, a decision support system based application, which facilitates a better approach in determining the feasibility of providing more depth insight of the ability of customers, can be a solution. One of the available methods to use is Simple Additive Weighting (SAW). This method allows value calculations to determine the feasibility of a request. The basic concept of SAW is to find out the weighted sum of performances in each alternative. The factors or criterias used in the study include the cutomers’ discipline, amount of down payment, monthly income, credit guarantees and residence status. On academic scope, the research can also be used as an enrichment of teaching materials especially in the Decision Support Systems course as well as information systems in general. The outcome of research is also expected to become one of references for students in implementing a decision support system in actual cases Keywords: Decision Support System, Simple Additive Weighting, Credit, Application